The Role of Forgiveness in Post-Traumatic Growth: A Cross-Sectional Study of Emerging Adults with Adverse Childhood Experiences - Anindhita Parasdyapawitra Amaranggani; Kartika Sari Dewi (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Adverse Childhood Experiences (ACEs) are associated with various negative impacts on the mental health of emerging adults. Previous studies have shown that post-traumatic personal growth after a particularly challenging event can be facilitated by the adoption of emotional coping strategies, such as forgiveness. This study examines the relationship between forgiveness and post-traumatic growth among emerging adults with ACEs in Indonesia. The sample consisted of 152 emerging adults, aged 18-25 years (M = 21.53; SD = 1.919), mostly female (92.1%), and reported at least one ACEs during their childhood. The instruments in this study were the WHO ACE-International Questionnaire, Post-traumatic Growth Inventory (21 items, α= 0.922) and the Forgiveness Scale (34 items, α = 0.935). Analysis was performed using Spearman's rho. The results of the study revealed that forgiveness was positively and significantly correlated with post-traumatic growth (rxy .471, p= .000). The originality of this study revealed that the three dimensions of forgiveness are strongly related to post-traumatic personal growth in ACEs survivors. This article expands the discussion on the inconsistency of the role of the forgiveness dimension towards others. Based on these results, the development of a forgiveness-based intervention to enhance post-traumatic personal growth for ACE survivors is proposed